Participation in After-School Extracurricular Activities and Cognitive Ability Among Early Adolescents in China: Moderating Effects of Gender and Family Economic Status - Pan, Yangu; Zhou, Di; Shek, Daniel Tan Lei (Frontiers in Pediatrics, 2022)
Although theories and research suggest that participation in extracurricular activities plays an important role in adolescents' cognitive development, few studies have addressed this issue among early adolescents in China. Based on the responses of 9,830 Chinese junior high school students (Mage = 14.54 years, SD = 0.70 years), we investigated the relationships between different types of extracurricular activities and cognitive ability among junior high school students and the related moderating effects of gender and family economic status. Using multi-level multiple regression analyses, results indicated that while time spent completing homework and physical exercise was positively associated with students’ cognitive ability, time spent on extracurricular tutoring, interest classes, watching TV, and surfing online and playing games was negatively related to students’ cognitive ability. The observed relationships were also moderated by gender and family economic status. Specifically, time spent on completing homework had a stronger positive relationship with boys’ cognitive ability, whereas time spent attending extracurricular tutoring on weekdays had stronger negative relationship with girls’ cognitive ability, and time spent on physical exercise was more strongly related to girls’ cognitive ability in a positive manner. Besides, time spent attending interest classes on weekdays had a stronger negative relationship with cognitive ability among students from wealthy families, and time spent watching TV and physical exercise had stronger negative and positive effects on the cognitive ability among students from economically disadvantaged families, respectively. The theoretical and practical implications of the findings regarding the role of extra-curricular activities on adolescent development are discussed.